Effects of Kefir as a Probiotic Source on the Performance and Health of Young Dairy Calves - Sema Satık; Mevlüt günal (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to investigate the effect of kefir as a probiotic on the performance and health status of calves. Thirty Holstein female calves with 3-day-old were randomly allocated to three treatment groups: Control (without any probiotic), probiotic (a commercial probiotic mixture-3 g/d/calf bacteria-based and 2 g/d/calf yeast-based) and kefir (20 ml/d/calf). The calves were weaned at 56 days of age. The experiment was performed in 70 days. Treatment had no effect (P>0.05) on weaning and final body weight and starter intake. Although differences in weight gain were not significant (P>0.05), there were trend to increase by probiotic treatments during 0-14 days. Probiotic treatments tended to have a positive effect on the population of the fecal lactic acid bacteria at 14 days. The results of the study indicated that kefir as a natural probiotic in calf nutrition may be beneficial during the first weeks of life.